Penerapan Aplikasi Sicantik Cloud Terhadap Kualitas Pelayanan di Dinas Penanaman Modal, Pelayanan Terpadu Satu Pintu dan Tenaga Kerja Kota Lhokseumawe - Rabiatul Adawiyah; Saiful Bahri; Syukri Syukri; Muhaddis Muhaddis (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia, 2024)
The management information system applied in the government is known as the term electronic government (e-government) which is interpreted as the user of information technology transforming government activities with the aim of increasing the effectiveness and efficiency of government administration. SiCantik Cloud is a smart application for integrated public cloud-based licensing services that can be used by government agencies independently. SiCantik Cloud or an intelligent application system for integrated licensing services for the public, is intended for the public to make it easier to manage online licensing. The purpose of this study is to determine the application of the Sicantik Cloud application to Services at the PMPTSP and Naker Office and the inhibiting factors for the application of the Sicantik Cloud application to Services at the PMPTSP and Naker Office of Lhokseumawe City. This study is a study using a qualitative descriptive approach. The application of the SiCantik application to the quality of service at the Investment, One-Stop Integrated Service and Manpower Office of Lhokseumawe City is quite good, as known from several benchmarks of service quality from the Sicantik Cloud application, namely Accountability, Transparency, Effectiveness, and Efficiency. The lack of public awareness of the importance of using information technology means that many people have not been able to optimize the Sicantik application.